A craniosynostosis massively parallel sequencing panel study in 309 Australian and New Zealand patients: findings and recommendations. (September 2018) - Lee, Eric; Le, Trang; Zhu, Ying; Elakis, George; Turner, Anne; Lo, William; Venselaar, Hanka; Verrenkamp, Carol-Ann; Snow, Nicole; Mowat, David; Kirk, Edwin Philip; Sachdev, Rani; et al.
Abstract Purpose The craniosynostoses are characterized by premature fusion of one or more cranial sutures. The relative contribution of previously reported genes to craniosynostosis in large cohorts is unclear. Here we report on the use of a massively parallel sequencing panel in individuals with craniosynostosis without a prior molecular diagnosis. Methods A 20-gene panel was designed based on the genes' association with craniosynostosis, and clinically validated through retrospective testing of an Australian and New Zealand cohort of 233 individuals with craniosynostosis in whom previous testing had not identified a causative variant withinFGFR1-3 hot-spot regions or theTWIST1 gene. An additional 76 individuals were tested prospectively. Results Pathogenic or likely pathogenic variants in non-FGFR genes were identified in 43 individuals, with diagnostic yields of 14% and 15% in retrospective and prospective cohorts, respectively. Variants were identified most frequently inTCF12 (N = 22) andEFNB1 (N = 8), typically in individuals with nonsyndromic coronal craniosynostosis orTWIST1 -negative clinically suspected Saethre–Chotzen syndrome. Clinically significant variants were also identified inALX4, EFNA4, ERF, andFGF10 . Conclusion These findings support the clinical utility of a massively parallel sequencing panel for craniosynostosis.TCF12 andEFNB1 should be included in genetic testing for nonsyndromic coronal craniosynostosis or clinically suspected Saethre–Chotzen syndrome.